Detection of α-thalassemia of southeast asian (-SEA) deletion by novel multiplex PCR - Wirawit Piyamongkol (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Background: Southeast Asian (-SEA) deletion of α-thalassemia is the most common α-thalassemia-1 mutation in Thailand and neighborhood countries. The absence of α-globin gene production in a homozygous fetus is the most serious and leads to death in utero or soon after birth and life-threatening maternal complications. Therefore, sensitive and accurate assays for detecting α-thalassemia-SEA deletion are crucial for thalassemia diagnosis.Materials and Methods: The present study evaluated multiplex polymerase chain reaction (PCR)-SEA, comparing with the routinely performed gap-PCR for α-thalassemia diagnosis in prenatal thalassemia prevention and control strategy commonly used in Thailand. Four primers were employed to detect the deleted region of α-globin gene family. This, thus, provides high accuracy in discriminating heterozygous and homozygous -SEA deletion. Results: Multiplex PCR-SEA assay showed the results with 100% sensitivity, specificity, positive predictive value, negative predictive value, and efficiency in comparison to the routinely performed gap-PCR used in prenatal thalassemia prevention and control strategy. In addition, the multiplex PCR-SEA assay displayed lower detection limit for heterozygous detection. Conclusion: The novel multiplex PCR-SEA in the present study was proofed to be a good alternative for thalassemia diagnosis in thalassemia prevention and control strategy. The advantage of the assay is the capability to identify three wild types and one deleted fragment comparing with one wild type and one deleted fragment in the routinely performed gap-PCR. This is very useful, especially in the genes where polymorphism is common. Therefore, the multiplex PCR-SEA provides a better protocol for α-thalassemia-SEA diagnosis.